2015
DOI: 10.2131/jts.40.873
|View full text |Cite
|
Sign up to set email alerts
|

Covalent binding of quinones activates the Ah receptor in Hepa1c1c7 cells

Abstract: -Highly reactive quinone species produced by photooxidation and/or metabolic activation of mono-or bi-aromatic hydrocarbons modulate cellular homeostasis and electrophilic signal transduction pathways through the covalent modification of proteins. Polycyclic aromatic hydrocarbons, but not mono-or bi-aromatic hydrocarbons, are well recognized as ligands for the aryl hydrocarbon receptor (AhR). However, quinone species produced from mono-and bi-aromatic hydrocarbons could potentially cause AhR activation. To cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…4 and 5). Similar results were described previously in Hepa1c1c7 cells (Abiko et al, 2015). We reported that activation of the Akt/CREB signaling pathway in response to MeHg, which is an environmental electrophile and easily bind to thiol groups on the cellular proteins, in SH-SY5Y cells followed a bell-shaped curve (Unoki et al, 2016).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…4 and 5). Similar results were described previously in Hepa1c1c7 cells (Abiko et al, 2015). We reported that activation of the Akt/CREB signaling pathway in response to MeHg, which is an environmental electrophile and easily bind to thiol groups on the cellular proteins, in SH-SY5Y cells followed a bell-shaped curve (Unoki et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…4B). Our previous study demonstrated that 1,2-NQ enhanced the interaction of AhR with ARNT in Hepa1c1c7 cells (Abiko et al, 2015). 1,2-NQ was a stronger AhR activator than TBQ.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations